A maddock mixer design that mitigates gels in polyethylene resin film applications. (April 2023) - Spalding, Mark A; Sun, Xiaofei; Kodjie, Stephen L; Du, Libo; Womer, Timothy W; Uzelac, Ned
Maddock mixers are ubiquitous in plastics processing for single-screw extruders and injection molding plasticators due to their low cost to build and their ability to provide a uniform level of dispersive mixing. If the mixer is designed properly, all entering solid polymer fragments and certain types of gels can be trapped and dispersed into the matrix resin. Many mixers that are used commercially, however, provide lower levels of dispersive stress mixing than required by the process and they can degrade polyethylene (PE) resins. This paper will describe the mechanisms that are occurring in a Maddock mixer and develop guidelines for obtaining optimal mixing stresses while mitigating resin degradation.